Differences in the palliative care phase between patients with nonmalignant pulmonary disease and lung cancer: a retrospective study - Hanna Pihlaja; Heidi A. Rantala; Silja Soikkeli; Milja Arminen; Sonja Aho; Sirpa Leivo-Korpela; Juho T. Lehto; Reetta P. Piili (BMC Palliative Care)
Abstract Background Patients with chronic nonmalignant pulmonary disease and lung cancer both need palliative care, but palliative care services may be better adjusted to serve cancer patients. We compared the timing and clinical practice of palliative care and acute hospital usage during the last year of life in patients with nonmalignant pulmonary disease or lung cancer. Methods This was a retrospective study of all patients in a palliative care phase (palliative goal of care) with nonmalignant pulmonary disease or lung cancer who were treated at Tampere University Hospital, Finland, during the years 2018–2020. The data were collected from the hospital’s medical records. Comparisons between the groups were performed by using the Pearson chi-square test, Fisher’s exact test, or Mann‒Whitney U test when appropriate. Survival was estimated by using the Kaplan‒Meier method. Results The study population consisted of 107 patients with nonmalignant pulmonary disease and 429 patients with lung cancer. Patients with nonmalignant pulmonary disease survived longer in the palliative care phase than patients with lung cancer (115 vs. 59 days, p < 0.001). Compared to lung cancer patients, patients with nonmalignant disease received a palliative care specialist consultation more often during hospitalization (66% vs. 45%, p < 0.001) than during a preplanned outpatient visit (6% vs. 52%, p < 0.001), were less likely to be referred to palliative care pathway (79% vs. 87%, p = 0.033), and spent more days in an acute care hospital during the last year of life (median of 10 vs. 6 days, p = 0.023). Contrary to lung cancer patients, referral to the palliative care pathway was not significantly associated with decreased acute hospital resource usage during the last month of life among patients with nonmalignant pulmonary disease. Conclusions Compared to lung cancer patients, patients with nonmalignant pulmonary disease had longer palliative care phases but fewer visits to the palliative care outpatient clinic and fewer referrals to the palliative care pathways. Palliative care arrangements seemed to have more influence on the end-of-life care of lung cancer patients. There is a need for long-term palliative care services with better abilities to meet the special needs of patients with nonmalignant pulmonary disease.